States of surveillance: ethnographies of new technologies in policing and justice - Avis, Maya; Marciniak, Daniel; Sapignoli, Maria (Routledge studies in surveillance, 2025)
Recent discussions on big data surveillance and artificial intelligence in governance have opened up an opportunity to think about the role of technology in the production of the knowledge states use to govern. The contributions in this volume examine the socio-technical assemblages that underpin the surveillance carried out by criminal justice institutions - particularly the digital tools that form the engine room of modern state bureaucracies.Drawing on ethnographic research in contexts from across the globe, the contributions to this volume engage with technologys promises of transformation, scrutinise established ways of thinking that becomeembedded through technologies, critically consider the dynamics that shape the political economy driving the expansion of security technologies, and examine how those at the margins navigate experiences of surveillance.The book is intended for an interdisciplinary academic audience interested in ethnographic approaches to the study of surveillance technologies in policing and justice. Concrete case studies provide students, practitioners, and activists from a broad range of backgrounds with nuanced entry points to the debate.The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution (CC-BY) 4.0 International license